Causes of root canal treatment failure: A prospective study in Makkah City, Saudi Arabia - Mohsen K Aljabri; Jamal A Kensara; Ayman O Mandorah; Monammed A Sunbul (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of the study is to identify the causes of root canal treatment (RCT) failures in Makkah City. Materials and Methods: The study used a prospective cohort study design, using a clinical examination, treatment, and follow-up. The study summarized the data of 131 patients presented to the Endodontic Department in King Faisal Hospital, Makkah, in the Western region of Saudi Arabia and included patients with failed RCT aged 16 years or older without any systemic disorder. Results: Of the 131 patients, the most common factor for root canal failure was underfilling (71.0%), followed by coronal leakage (42.7%), overfilling (16.8%), missed canal (16.0%), iatrogenic (6.1%), leaked canal and anatomic (1.5%), and 3.1% for unknown causes. Fifty-two (39.7%) were female and 79 (60.3%) were male. One hundred and three (78.6%) were 18-40 years old, whereas 28 (21.4%) were 40 years old and older. For tooth type, 34 (26.0%) had an anterior root canal, 39 (29.8%) had a molar root canal, and 58 (44.3%) had a premolar root canal. Conclusion: Considering the limitations of the present study, it was determined that endodontic treatment failures mostly occurred in underfilled root canals, followed in number by coronal leakage. Premolars had a higher failure rate than did anterior and molar teeth.